A Parallel Interpolation Subdivision Scheme for Curve and Surface Design (Journal of Fiber Bioengineering and Informatics, 2015)
This paper proposes a new scheme of interpolation subdivision curve and surface using Bezier curve\rto achieve more realistic surface design. Different from the previous interpolation subdivision schemes,\rthe normal vectors are used to generate a circle from a triangle which results in only three vertices and\rthree edges. This improvement not only makes a curve smooth, but also produces sharp angles during\rsubdivision. Examples of subdivision surface by this scheme are illustrated and compared to show the\radvantages of this scheme.
Keywords: Interpolation Subdivision; Normal Vectors; Bezier Curve; Parallel Computation